Cross-talk between gibberellins and salicylic acid in early stress responses in Arabidopsis thaliana seeds - Alonso-Ramírez, Ana (Landes Bioscience, 2009)
Salicylic acid (SA) is a plant hormone mainly associated with the induction of defense mechanism in plants, although in the last years there is increasing evidence on the role of SA in plant responses to abiotic stress. We recently reported that an increase in endogenous SA levels are able to counteract the inhibitory effects of several abiotic stress conditions during germination and seedling establishment of Arabidopsis thaliana and that this effect is modulated by gibberellins (GAs) probably through a member of the GASA (Giberellic Acid Stimulated in Arabidopsis) gene family, clearly showing the existence of a cross talk between these two plant hormones in Arabidopsis.